Investigating the Effect of Low-Yield Yielding Dampers on the Seismic Behavior of Steel Frames - Cheraghi, Kambiz; Tavana, Mohammad Hadi; Aghayari, Reza (Periodica Polytechnica Civil Engineering, 2023)
Yielding dampers operate based on plastic deformations and energy dissipation. Given its low yield stress point and high ductility, low-yield steel is a suitable choice to build yielding dampers. In the present study, using the ABAQUS software, a number of pushover analyses have been carried out on a steel frame equipped with low-yield yielding dampers (LYDs). Therefore, using 40 pushover analyses, the effects of the number of the LYDs and the column’s axial force have been evaluated. All of the models were analyzed and their force-displacement curves were obtained. Using the obtained, different seismic aspects of the frame – i.e., ductility, strength, energy dissipation, stiffness – were assessed. Also, to calculate the values of effective stiffness and yield and ultimate strengths, a number of analytical relationships have been formulated. Finally, contour plots have been obtained which can be used to calculate the stiffness of the proposed LYD. Comparing results showed that the damper can, to an acceptable level, improve the seismic parameters of the structure. Also, if the stiffness and yield strength of all of the LYDs added to the frame are, respectively, 3.25 and 0.13 times those of the bare frame, the frame will have its best performance.